The Role of Media Literacy in Shaping Public Opinion and Political Participation in the Digital Era - El Emary, Ibrahiem M. M.; Alhebbi, Mohammed Ahmed (International Journal of Informatics and Information Systems, 2025)
The rapid development of digital technology has transformed how people access, interpret, and respond to political information. This study explores the role of media literacy in shaping public opinion and political participation in the digital era. Using a descriptive qualitative approach, data were collected through in-depth interviews with ten respondents from diverse educational and social backgrounds. The findings reveal that individuals with higher media literacy demonstrate stronger critical thinking, higher awareness of information credibility, and greater involvement in political discourse and civic engagement. Conversely, those with lower media literacy are more susceptible to misinformation, hoaxes, and emotional manipulation, which can distort political perceptions and reduce participation. The study highlights that media literacy not only enhances citizens’ ability to filter and evaluate political content but also strengthens democratic quality by encouraging informed and responsible participation. It recommends that media literacy education be integrated into both formal and informal learning environments to foster critical, active, and digitally responsible citizens.